2022
DOI: 10.3389/fphar.2022.827244
|View full text |Cite
|
Sign up to set email alerts
|

Title: P2x7 Receptor Activation and Estrogen Status Drive Neuroinflammatory Mechanisms in a Rat Model for Dry Eye

Abstract: Dry eye disease (DED) is recognized as a chronic inflammatory condition with an increase in tear osmolarity and loss of tear film integrity. DED is often accompanied by adverse ocular symptoms which are more prevalent in females than males. The basis for ocular hyperalgesia in DED remains uncertain; however, both peripheral and central neural mechanisms are implicated. A model for aqueous deficient DED, exorbital gland excision, was used to determine if activation of the purinergic receptor subtype 7, P2X7R, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…28 As a result, activated microglia amplify the sensory transmission pathway's excitability, leading to bodily pain. 7 This framework aptly elucidates our observed c-fos expression surge and provides a rationale for the resultant ocular pain, aligning with Kikuchi's perspectives. 29 The suppression of TNF-α has been demonstrated to alleviate pain and hyperalgesia in animal models related to pain.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…28 As a result, activated microglia amplify the sensory transmission pathway's excitability, leading to bodily pain. 7 This framework aptly elucidates our observed c-fos expression surge and provides a rationale for the resultant ocular pain, aligning with Kikuchi's perspectives. 29 The suppression of TNF-α has been demonstrated to alleviate pain and hyperalgesia in animal models related to pain.…”
mentioning
confidence: 72%
“…This activity subsequently ignites microglia and triggers the release of a plethora of inflammatory factors. 6 Such inflammation not only inflicts neuronal damage 7 but also incites sensitization in both surrounding and central nervous systems. 8 This cascade establishes the pathological foundation of DE ocular pain.…”
Section: Introductionmentioning
confidence: 99%
“…Animals (Sprague-Dawley male rats, 220–250 g, Taconic, USA) were housed in pairs with food and water available ad libitum under a constant 12-hour light/dark cycle (lights on at 7:00 am) at room temperature. To avoid the potential effects of the periodic increase in estrogen on purinergic signaling and P2X7 expression [2; 7; 17], we studied only male rats to ensure the uniformity and repeatability of experiments. All procedures and testing were conducted during the light phase of the cycle (9:00 am to 4:00 pm).…”
Section: Methodsmentioning
confidence: 99%
“…[ 50 ] Another study reported that microglia isolated from DED mice showed higher expression of P2X7R and P2X4R along with inflammatory factors. [ 67 ] Orbicularis oculi muscle activity studied in animal models with DED is similar to ocular irritation and pain in DED patients and eyelid squint in awake subjects following exposure to adverse ocular stimuli. It is also found that P2X7R blockade using an antagonistic or expression knockdown resulted in reduced mRNA expression of P2X7R and P2X4R, along with reduction in the hypertonic saline-induced orbicularis oculi muscle activity in DED animals.…”
Section: Ligand-gated Ion Channelmentioning
confidence: 99%
“…It is also found that P2X7R blockade using an antagonistic or expression knockdown resulted in reduced mRNA expression of P2X7R and P2X4R, along with reduction in the hypertonic saline-induced orbicularis oculi muscle activity in DED animals. [ 67 ]…”
Section: Ligand-gated Ion Channelmentioning
confidence: 99%